Pathological response of a mouse model of lethal Vibrio vulnificus infection and its preliminary application in inactivated whole cell vaccine - ZHU Baohang; PAN Jiale; LIU Shulin (陆军军医大学学报)
‍Objective‍　‍To establish a mouse model of infection with the minimum lethal dose of Vibrio vulnificus (V. vulnificus) and to evaluate the protective efficacy of inactivated whole-cell (IWC) vaccine using this model. Methods‍　‍A mouse model of lethal-dose infection was established by intraperitoneal injection of different doses of V. vulnificus. Bacterial colonization in the organs was detected with tissue homogenate plating, and pathological changes in the organs were observed after tissue section staining. Flow cytometry was used to detect immune cell responses after liver tissues were digested into single-cell suspension. IWC vaccine of V. vulnificus was prepared, and the mice were immunized through different routes to observe the protective efficacy of the vaccine. Results‍　‍A mouse model of infection with the minimum lethal dose at 1×106 CFU of V. vulnificus was successfully established. After infection, the bacteria were mainly colonized in the liver of mice and caused severe pathological damages. Compared with the uninfected mice, the proportion of neutrophils in the liver was significantly increased in the infected mice, whereas the proportions of B cells and T cells were correspondingly decreased (P<0.05). A single intramuscular or intraperitoneal injection of the IWC vaccine could protect the mice effectively against lethal infection of V. vulnificus in 7 d later (P<0.01), although the level of serum IgG having no significant increase. Conclusion‍　‍A mouse model of lethal-dose infection with V. vulnificus is successfully established, with histopathological characteristics. The IWC vaccine of V. vulnificus rapidly mediates immune protection in this model probably independent of IgG.